Latex-Fruit Syndrome in Italian Children and Adolescents with Natural Rubber Latex Allergy. (January 2013) - Ricci, G.; Piccinno, V.; Calamelli, E.; Giannetti, A.; Pession, A.
Approximately 30–50% of individuals with natural rubber latex (NRL) allergy show an associated hypersensitivity to particular plant-derived foods, which has been defined "latex-fruit syndrome" (LFS). In our population of 22 patients with IgE-mediated NRL allergy we found a relevant prevalence (36%) of LFS, which resulted significantly higher in the group of patients with more severe clinical manifestations of NRL allergy than in patients with contact symptoms due to NRL (78% vs 8%; p <0.005).